PENGARUH KOMITMEN ORGANISASI, IKLIM ORGANISASI, BUDAYA ORGANISASI DAN PERSON ORGANIZATIONAL FIT TERHADAP KINERJA PEGAWAI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KERINCI - Leni Edmizar; Romi Delmaira; Nelpa Dewenti; Afriyeni Afriyeni (Jurnal Bina Bangsa Ekonomika, 2024)
This study aims to determine the effect of organizational commitment, organizational climate, organizational culture and person organizational fit (POF) on the performance of Disdukcapil employees of Kerinci Regency. The method used in this study is quantitative research with a descriptive approach. The population in this study is all employees of Disdukcapil Kerinci Regency. The sample used was 32 people using  saturated sampling  techniques (census). The data analysis technique is multiple linear regression. The results showed that: (1) Organizational commitment has a positive and significant effect on the performance of Disdukcapil employees of Kerinci Regency. (2) The organizational climate has a positive and significant effect on the performance of Disdukcapil employees of Kerinci Regency. (3) Organizational culture has a positive and significant effect on the performance of Disdukcapil employees of Kerinci Regency. (4) POF has a positive and significant effect on the performance of Disdukcapil employees of Kerinci Regency. (5) Organizational commitment, organizational climate, organizational culture and POF together have a positive and significant effect on the performance of Disdukcapil employees of Kerinci Regency